PENGARUH KEMAMPUAN APARATUR DESA TERHADAP PERENCANAAN PEMBANGUNAN DESA PANGU SATU KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA - KALIGIS, REIVANA; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Development aims to create a just and prosperous, and prosperous society. In the implementation of thedevelopment to be in accordance with the objectives set, the implementation is greatly supported by goodmanagement and organization. One of the management processes is planning. Without a plan, there is nobasis for carrying out activities in development activities in the context of achieving goals. This study aimsto determine the effect of the ability of the apparatus on village development planning Pangu Satu. Thisstudy uses quantitative research using the dimensions of technical, social and conceptual abilities for thecapability variables and the dimensions of preparation, implementation and institutionalization for theplanning variables for data collection techniques, namely questionnaires or questionnaires, observationand documentation. This research uses simple linear regression analysis. The results of this study are thatthe ability of the apparatus has a positive effect on village development planning. The conceptual ability ofthe government in development planning is in accordance with the procedure but the quality of theprocess is still not optimal, Cooperation and coordination of the village government with village officialsare not going well.Keywords: Ability, Planning, Development